Study on the Pore Structures and Adsorption Characteristics of Coking Coal of Liulin Mining in China Under the Condition of High Temperature and High Pressure - Lingling, Qi; Xinshan, Peng; Zhaofeng, Wang; Xiangjun, Chen; Juhua, Dai (Frontiers in Earth Science, 2022)
In order to study the change of pore structure and adsorption characteristics of coking coal when after high temperature and high pressure adsorption test, the coking coal from Liulin coalmine was selected for the research. Both the mercury injection experiments were carried out on the raw coal and the coal after the isothermal adsorption experiment processing with pressure of 11MPa and temperature from 30℃ to 90 ℃. The results show that, the pressure is beneficial to the gas adsorption, while the temperature has a restraining effect on the gas adsorption of coking coal, and there is a good negative exponential relationship between the adsorption capacity and the temperature. The hysteresis loop of that after high temperature and high pressure isothermal adsorption test is smaller than that of raw coal, and the connectivity of pores becomes worse. In the process of mercury injection experiment, the hysteresis loop of coking coal after high temperature and high pressure adsorption experiment is smaller than that of raw coal. This demonstrates that the open pores decrease, and the semi-closed pores increase, and then the connectivity of the pores becomes worse, which is not conducive to the gas flow when the coking subjected to the high temperature and high pressure action. After the high temperature and high pressure adsorption experiment, The volume of macropores, visible pores and crannies of the coking coal decreases, and the micropores and minipores increases. However, the total pore volume reduction overall. Under the same pressure, with the increase of temperature, the volume of macropores, visible pores and crannies increases, the micropores and minipores decreases, and the total pore volume increases. After the high-temperature and high-pressure adsorption experiment, the proportion of micropores and minipores increase, and also the specific surface area. Under the same pressure, the surface areas of micropores and minipores decrease and also the total specific surface area with the increase of temperature.